The Effectiveness of Using Talking Stick for Teaching Speaking - One Lintang Fatt’ah (UM Purwokerto Press, 2024)
This study aims to investigate the effectiveness of Talking Stick Game in teach pronunciation in Junior High School. In this study, an experimental research approach was utilized, and the participants were students in the 8th grade at SMP N 1 Kemangkon, with a total of sixty-four students participating. The data collection method used is a test, which is divided into two, namely pretest and posttest with a sentences and dialog to pronounce for each test instrument. The data analysis technique used was t-test. The null hypothesis (HO) is rejected and the alternative hypothesis (HI) is also rejected. It meant that there was unsignificant difference between the students pronunciation before and after using Talking Stick Game. In brief, Talking Stick Game is not effective ways in teaching pronunciation